AN ANALYSIS OF MORAL VALUE IN 47 RONIN FILM - Yohanes Johardianto (Fakultas Bahasa dan Sastra Universitas Kanjuruhan Malang, 2018)
We have been quite familiar with art and literary work in our life. They can be music, pain or literature. Literature is human expression consisting experience, consideration, feeling, idea, spirit, and conviction in form of concrete description that arouse attraction by using language. Literature is the result of ideas that belongs to human. The result of literary works can be written work , pictures or music. Literary works in written form include the novel, poem, short story, verse, etc. While in pictures form include painting, movie, photograph, etc. And literary works in the form of music include songs that every day we listen. This thesis is an effort to analyze the moral values in the movie entitled “47 Ronin”, which might be very useful for the researcher himself, the readers, and other researchers who might need it as source of information. There are three research problems proposed from this “47 Ronin” analyzing film. They are: (1) The moral value found on this film, (2) The moral values conveyed on this film, (3) The messages that can be delivered to the viewers. Based on the result of this study the researcher found some moral values contained in the movie”47 Ronin”, such as: friendliness, tolerance and acceptance, self-confidence, determination, honesty, positive attitude, patience, initiative and courage, motivation, self respect. The researcher hopes those values would be useful for the Viewers and the readers of this thesis as their life guidance to be better persons. Keywords: Moral Value, “47 Ronin” Film